An Exception to the Gender Gap in Education : The Middle East? - Ezzine, Mourad; Thacker, Simon; Chamlou, Nadereh (World Bank, Washington, DC, 2012)
An interesting consequence of the Arab Spring is that it is compelling the West to re-evaluate its understanding of the Middle East. Stereotypes and misconceptions have abounded, but today the region can no longer be grossly dismissed as home only to extremists or the oil-rich. Instead, a more nuanced and accurate picture is emerging: one that is as full of contradictions as an image of any region will be. For a region not known for its equitable attitudes towards women, for instance, the Middle East offers up some surprising results for girls in school, results that are much better in some ways than the rest of the world.